Expression patterns of Toll-like receptors in the ovine corpus luteum during the early pregnancy and prostaglandin F2α-induced luteolysis - Atli, Mehmet O.; Kose, Mehmet; Hitit, Mustafa; Kaya, M. Salih; Bozkaya, Faruk (Elsevier BV, 2018)
The aim of this study was to elucidate the expression profiles of Toll-like receptors (TLRs) in the ovine corpus luteum (CL) during early pregnancy and prostaglandin F2α (PGF2α)-induced luteolysis. For this purpose, multiparous Anatolian Merino ewes were selected and randomly allotted into cyclic (including those in the induced luteolysis group, n = 20) and pregnant (n = 12) groups. All of the ewes were scheduled to be slaughtered for predetermined days/hour during the estrous cycle, early pregnancy, and PGF2α induced luteolysis. The CLs were collected from both cyclic and pregnant ewes on days 12 (C12 and P12; n = 8) and 16 (C16 and P16; n = 8) and pregnant ewes on day 22 (P22; n = 4). For the induced luteolysis model, ewes were injected with PGF2α on day 12 of the estrous cycle and CLs were collected at 1 h (PG1h; n = 4), 4 h (PG4h; n = 4), and 16 h (PG16h, n = 4) after injection. Quantitative polymerase chain reaction (qPCR) was used to evaluate the expression profiles of TLR2, TLR4, TLR6, TLR8, and TLR10, while free-floating in situ hybridization and immunohistochemistry were used to define the spatial localization of TLR2, TLR4, and TLR7 in the CL. Data were then analyzed by one-way ANOVA and were considered statistically significant when P values were lower than 0.05. Expression of TLR2 was upregulated in both early and late stages of luteolysis (P < .05). An upregulation of TLR4 was detected at PG16h, while TLR6 was decreased at PG4h (P < .05). Expression of TLR7 and TLR8 was significantly increased during early pregnancy, at both PG16h and regressed groups (C16, P < .05). In contrast, TLR10 was downregulated during PGF2α-induced luteolysis and on P16 (P < .05). TLR4 and TLR7 proteins were particularly localized in endothelial cells on C12/PG0h, but prominent signals corresponding to TLR4 and TLR7 were detected in luteal cells at PG16h. The results suggest an involvement of TLRs in the luteolytic mechanism in ovine CL, as indicated by differential expression levels of TLRs during PGF2α-induced luteolysis. Moreover, the present study indicates that early pregnancy-mediated changes in TLR expression in the CL may contribute to the establishment and maintenance of ovine pregnancy.
Keywords: Sheep; Toll-Like Receptors; Dinoprost; Ovine; Gene Expression Regulation; Corpus Luteum; Pregnancy; Animals; Pregnancy, Animal; Female; RNA, Messenger